GOVERNANCE STRATEGIES TO PROMOTE HEALTH AND WELL-BEING: URBAN BLUE SPACE INFRASTRUCTURE INITIATIVES IN PLYMOUTH (UK). Issue 2 (4th May 2021) - Adade, Evelyn A; R Elliott, Lewis; Fleming, Lora E; Wuijts, Susanne
ABSTRACT: Building on evidence of the links between bluespace and public health, this study explores the governance of bluespace infrastructure to promote human health and well-being in Plymouth (UK). Using in-depth retrospective interviews and document analysis, this study focused on the role of governance in urban planning and development, specifically, the implementation phase of a bluespace infrastructure intervention. A deductive qualitative approach categorised content into themes related to pre-established water governance frameworks. Key findings from this study emphasise: the importance of health and welfare concerns around blue spaces as an incentive to getting started; collaborative stakeholder participation and engagement; the necessity of adequate funding; and the importance of continued monitoring and maintenance of urban blue space infrastructure. Based on reflective accounts of stakeholder experiences, the successes of the implementation process of the redevelopment are highlighted. More successful and sustainable bluespace interventions can be realised through ongoing considerations of effective water governance.